2021
DOI: 10.1007/s43440-021-00296-2
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on intravenous N-Acetylcysteine treatment in patients with mild-to-moderate COVID19-associated acute respiratory distress syndrome

Abstract: Background We designed this single-centre clinical trial to assess the potential benefits of N-Acetylcysteine (NAC) in patients with COVID19-associated acute respiratory distress syndrome (ARDS). Methods Ninety-two patients with mild-to-moderate COVID19-associated ARDS were allocated to the placebo (45-cases) or NAC groups (47-cases). Besides standard-of-care treatment, the patients received either intravenous NAC at a dose of 40 mg/kg/day or the placebo for three consecutive days. The efficacy outcomes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 47 publications
4
58
0
2
Order By: Relevance
“…Another study that enroled 92 patients with COVID-19-associated ARDS was unable to find difference in the 28-day mortality rate between the group treated with NAC at an intravenous dose of 40 mg/kg/day as an adjunct therapy (25.5%) and that treated with placebo (31.1%) [72].…”
Section: Evidence For Use Of Thiols In Covid-19mentioning
confidence: 98%
“…Another study that enroled 92 patients with COVID-19-associated ARDS was unable to find difference in the 28-day mortality rate between the group treated with NAC at an intravenous dose of 40 mg/kg/day as an adjunct therapy (25.5%) and that treated with placebo (31.1%) [72].…”
Section: Evidence For Use Of Thiols In Covid-19mentioning
confidence: 98%
“…Beneficial effects of N-acetylcysteine have been demonstrated in clinical trials in various infections, including influenza and influenza-like infections, namely H1N1 influenza pneumonia or even community acquired pneumonia (De Flora et al, 1997;Zhang et al, 2018). In COVID-19, administration of N-acetylcyteine, alone or together with other types of supplementation may be beneficial in patients with different degrees of severity of SARS-CoV-2 infection, as suggested by a few small-sized, non-controlled clinical interventional studies or case reports (De Flora et al, 2020;Avdeev et al, 2021;Wong et al, 2021), although these results may not apply to patients with SARS-CoV-2-induced ARDS (de Alencar et al, 2021;Taher et al, 2021), and still need to be more robustly analysed in larger, randomised, placebo-controlled studies.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Taher et.al conversely reported that IV-NAC administration showed positive impact but did not show significant results in the treatment of critical COVID-19 patients [1003]. Taher et.al in their study of 92 patients administered 47 patients with IV-NAC and treated the other 45 people as placebo.…”
Section: (Intravenous N-acetyl-cysteine) Iv-nac When Administered Properly Might Enhance Covid-19 Patient's Condition By Reducing Inflammmentioning
confidence: 95%
“…Taher et.al in their study of 92 patients administered 47 patients with IV-NAC and treated the other 45 people as placebo. These patients were followed up for 28 days [1003]. But in the study Taher et.al [1003] have followed only a 3-day treatment protocol [1003].…”
Section: (Intravenous N-acetyl-cysteine) Iv-nac When Administered Properly Might Enhance Covid-19 Patient's Condition By Reducing Inflammmentioning
confidence: 99%
See 1 more Smart Citation